The Role of Indigenous Vegetables to Improve Food and Nutrition Security: Experiences From the Project HORTINLEA in Kenya (2014–2018) - Bokelmann, Wolfgang; Huyskens-Keil, Susanne; Ferenczi, Zoltan; Stöber, Silke (Frontiers in Sustainable Food Systems, 2022)
Many warning signs indicate that the food security goals formulated in 2015 will not be achieved. This situation is particularly true for the African continent. After substantial progress up to 2015, the situation has hardly improved or has worsened in many respects. In addition to the rapid population growth, the increasingly frequent long dry periods or sometimes erratic rainfall have contributed to this. In addition, current production systems have dysfunctional side effects due to increasing yield optimization and specialization. Thus, besides the associated resource degradation, it also leads to a monotonous food supply and the emergence of vitamin and mineral deficiencies (hidden hunger). A meaningful way to diversify the food supply is to cultivate and market previously underutilized species. However, they are characterized by not being known and traded globally and usually having only local importance. Accordingly, they have been widely ignored in research. Increasingly, however, there is a growing realization worldwide that these plants can make an essential contribution to food and nutrition security, especially for poorer segments of the population. Moreover, they are adapted to local conditions and are often produced with less resource input. This article aims to show how these species can be better utilized to provide nutritious food through sustainable production, using the example of African indigenous vegetables. In doing so, the impact of emerging social and ecological changes in Kenya will be considered. This source is an interdisciplinary collaborative research project, Horticultural Innovation and Learning for Improved Nutrition and Livelihood in East Africa (HORTINLEA), which was carried out in Kenya from 2014 to 2018. Many different disciplines were involved in the German-African cooperation project. The results will be brought together in this article with the help of a food-sensitive value chain approach, and the experiences gained from this project will be reflected.